Android Based Tani Rahayu Application Uses Extreme Programming (Xp) Method - Bagus Aidi; Meriska Defriani; Irsan Jaelani (RISTEC : Research in Information Systems and Technology, 2023)
Abstract: As many smartphone users with the Android operating system in this digital era applications become one of the tools that can help users in various ways, one of which is to buy necessities, this can be used in companies that usually sell their products in stores that often need effort for consumers to get products. CV. Cipta Rahayu is a company engaged in the sale of agricultural materials, the manual sales process often causes problems such as in processing transaction data, and it takes a long time to make reports, and at least customers because customers have to come directly to the location to order goods, after that it is processed and delivered to the customer's location, this will be difficult for customers whose position is far from the CV location, Often customers also choose to buy goods in the nearest place at a much more expensive price. Therefore, the company needs a mobile application sales system with the name Tani Rahayu application that can facilitate the sales process. The purpose of this research is to design and build an Android-Based Rahayu Farmer Application Using the Extreme Programming (XP) Method. The result of this study is the creation of the Android-based Tani Rahayu application, which will make it easier for customers to order goods without having to go to stores that take distance and time, then solve problems with shop owners or CVs in the process of customer orders and bookkeeping, then overcome customers switching to purchasing agricultural materials at other stores due to the remote location of the store, and attract many more other customers.